2013
DOI: 10.1161/strokeaha.111.000188
|View full text |Cite
|
Sign up to set email alerts
|

The Intracerebral Hemorrhage Acutely Decreasing Arterial Pressure Trial

Abstract: Background and Purpose— Acute blood pressure (BP) reduction aimed at attenuation of intracerebral hemorrhage (ICH) expansion might also compromise cerebral blood flow (CBF). We tested the hypothesis that CBF in acute ICH patients is unaffected by BP reduction. Methods— Patients with spontaneous ICH <24 hours after onset and systolic BP > 150 mm Hg were randomly assigned to an intravenous antihypertensive treatment protocol targeting a systolic BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 24 publications
5
124
1
3
Order By: Relevance
“…We found similar myogenic responsive patterns in both in vivo and in vitro conditions that were clinically reminiscent of, first, adjusting high systemic blood pressure in patients after hemorrhagic stroke 14, 30. Interestingly, a recent clinical trial indicated that an acute reduction of systemic blood pressure did not significantly improve CBF to surrounding brain areas after hemorrhagic shock 31. The outcomes correspond to our findings showing that the enhanced myogenic constriction in response to exposure of arterioles to hemolyzed blood was present in a relatively lower pressure range (corresponding to 40–120 mm Hg systemic blood pressure), implying that lowering systemic blood pressure may not be sufficient to overcome enhanced myogenic constriction after hemorrhage.…”
Section: Discussionsupporting
confidence: 58%
“…We found similar myogenic responsive patterns in both in vivo and in vitro conditions that were clinically reminiscent of, first, adjusting high systemic blood pressure in patients after hemorrhagic stroke 14, 30. Interestingly, a recent clinical trial indicated that an acute reduction of systemic blood pressure did not significantly improve CBF to surrounding brain areas after hemorrhagic shock 31. The outcomes correspond to our findings showing that the enhanced myogenic constriction in response to exposure of arterioles to hemolyzed blood was present in a relatively lower pressure range (corresponding to 40–120 mm Hg systemic blood pressure), implying that lowering systemic blood pressure may not be sufficient to overcome enhanced myogenic constriction after hemorrhage.…”
Section: Discussionsupporting
confidence: 58%
“…15,17,31 In the present study, we found no relationship between BP treatment target or actual BP and perihematoma CPP. The maintenance of CPP despite marked reductions in BP in many of our patients suggests some preservation of autoregulation in patients with acute ICH.…”
Section: Blood Pressure and Perihematoma Perfusion Pressurecontrasting
confidence: 63%
“…16 In the Intracerebral Hemorrhage Acutely Decreasing Arterial Pressure Trial (ICH ADAPT), we demonstrated that acute BP reduction is not associated with a significant fall in CBF. 17 It has been demonstrated, however, that CPP is more sensitive than CBF or CBV to changes in blood pressure. 18 The relationship between CPP and BP reduction in patients with intracerebral hemorrhage is unknown.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurement of the uptake rate of oxygen with 15 O-labeled water PET scan remains the gold standard for assessment of metabolic rate, and a more rigorous validation study of the flow heterogeneity technique in stroke patients remains outstanding. In addition, the maps generated in our study indicate that CBF and metabolism vary with tissue type.…”
Section: Blood Pressure and Perihematoma Metabolismmentioning
confidence: 99%